2009
DOI: 10.1088/0004-637x/703/1/150
|View full text |Cite
|
Sign up to set email alerts
|

Active Galactic Nuclei and the Truncation of Star Formation in K+a Galaxies

Abstract: We have searched for active galactic nuclei (AGNs) in K+A galaxies, using multiwavelength imaging and spectroscopy in the Boötes field of the NOAO Deep Wide-Field Survey. The K+A galaxies, which have had their star formation rapidly truncated, are selected via their strong Balmer absorption lines and weak Hα emission. Our sample consists of 24 K+A galaxies selected from 6594 0.10 < z < 0.35 galaxies brighter than I = 20 with optical spectroscopy from the AGN and Galaxy Evolution Survey. Two thirds of the K+A g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(53 citation statements)
references
References 60 publications
(120 reference statements)
5
48
0
Order By: Relevance
“…However, their location in the upper right corner of the UVgz diagram is consistent with little or no dust extinction(cf. Balogh et al 2005;Kaviraj et al 2007;Brown et al 2009;Chilingarian & Zolotukhin 2012;Whitaker et al 2012). We also showed in Figure 5 that about 80% of QPSBs do not show significantly dust-obscured star formation (have f 12 μm /f 0.2 μm < 200).…”
Section: A2 the Color-color Diagram: The Intrinsic Colors Of Obscursupporting
confidence: 61%
See 1 more Smart Citation
“…However, their location in the upper right corner of the UVgz diagram is consistent with little or no dust extinction(cf. Balogh et al 2005;Kaviraj et al 2007;Brown et al 2009;Chilingarian & Zolotukhin 2012;Whitaker et al 2012). We also showed in Figure 5 that about 80% of QPSBs do not show significantly dust-obscured star formation (have f 12 μm /f 0.2 μm < 200).…”
Section: A2 the Color-color Diagram: The Intrinsic Colors Of Obscursupporting
confidence: 61%
“…These sources are mostly low-luminosity AGNs at best and have a hard mean stacked X-ray spectrum suggesting moderate levels of obscured AGN activity in the bulk of this population. Similarly, Brown et al (2009) have found that one-third (8/24) of their K+A galaxies at z ∼ 0.2 are X-ray sources with luminosities of ∼10 42 erg s −1 . To improve on these previously incomplete estimates of the AGN fraction in post-starbursts, we assemble a large and less biased sample of post-starbursts, which includes emissionline galaxies, to robustly identify AGNs.…”
Section: Finding All Agns Including a Population Of Highly Obscured mentioning
confidence: 78%
“…Many studies into post-starbursts have aimed to confirm the presence of AGNs in these systems. Brown et al (2009) observed a slight enhancement in X-rays in a sample of K+A galaxies in the NOAO Deep Wide-field Survey, though not to a significance to be definitively from AGN emission. Shin et al (2011) cross-identify 1.4 GHz FIRST (Becker et al 1995) sources with the Goto (2007) E+A sample, but detections are ambiguous (most sources unresolved and lacking clear radio jets).…”
Section: Agns In Post-starburstsmentioning
confidence: 81%
“…Although the SDSS spectroscopy aims to be 100% complete at r=17.77 (Strauss et al 2002), we find that our sample is ∼80% complete at this level, as shown in Fig.1. Most studies of post-starbursts use a typical S/N of 3-5 in the continuum, as evidenced by Pracy et al (2005) (S/N>5); Couch & Sharples (1987) (S/N>3) and Brown et al (2009) (S/N>4), hence we adopt a minimum S/N of 5.…”
Section: Sample Selectionmentioning
confidence: 99%